Bangladesh Rural Advancement Committee statement of accounts for the year ended December 31, 1978 - BRAC (© BRAC, 2016)
This Financial Statement prepared by Rahman Rahman Huq & Co. Chartered Accountants, Dacca, Bangladesh.